Critical Discourse Analysis (CDA) Using Teun A. van Dijk’s Model on the “Kabur Aja Dulu” Hashtag in the Kompas.com News Channel - Christina Purwanti; I Nengah Suandi; I Nyoman Sudiana; I Putu Mas Dewantara (International Journal of Multilingual Education and Applied Linguistics, 2025)
This study aims to analyze the discourse framing of Kompas.com news texts related to the hashtag “Kabur Aja Dulu”, which was published in the period 17 February - 17 March 2025. This research is a descriptive qualitative research with Teun A. Van Dijk analysis model. The research data was obtained through digital documentation of Kompas.com articles using the hashtag “Kabur Aja Dulu”, then analyzed through three main stages: data reduction, data presentation, and conclusion drawing. The analysis was conducted systematically using Van Dijk's structural framework which includes three levels of analysis: macro structure, superstructure, and microstructure. The analysis shows that Kompas.com tends to use language and interview techniques that reflect the government's perspective, with complex discourse framing patterns that reflect power dynamics in news production. Through the analysis of Van Dijk's model, it can be seen that the media uses various linguistic and structural strategies to build a narrative that is in line with the government's perspective, including the use of formal language, structured interview techniques, and the construction of a strong narrative about the urgency of handling the phenomenon. Overall, this study reveals how the mass media play an important role in the social construction of reality through the way they frame and convey information to the public.